Clinical impact of A/H1/N1/09 influenza in patients with cirrhosis: Experience from a nosocomial cluster of infection12. Issue 1 (14th November 2012) - Marzano, Alfredo; Marengo, Andrea; Ruggiero, Tina; Allice, Tiziano; Sanna, Claudia; Alessandria, Carlo; Morgando, Anna; Sciandrello, Maria Clotilde; Franzin, Anna Maria; Rizzetto, Mario; Ghisetti, Valeria
Abstract A/H1N1/09 influenza is associated with a high risk of complications in patients with chronic diseases, but data on morbidity and mortality in patients with cirrhosis are limited. A cluster of A/H1N1/09 infection in 48 patients admitted to a Gastro‐Hepatology Unit is reported. Nosocomial spread, clinical outcome, and viral characteristics of A/H1N1/09 strains from a study group of 48 inpatients (21 and 27 with and without cirrhosis, respectively) were compared with those from a control group of 44 outpatients with mild influenza‐like illness and without cirrhosis. A/H1N1/09 infection was confirmed in 8/48 (17%) inpatients. A/H1N1/09 infection rate did not differ in patients with and without cirrhosis (4/21, 19%; 4/27, 15%), but three patients with cirrhosis died of pneumonia and acute respiratory distress syndrome, with fungal or bacterial superinfection in two cases, despite antiviral treatment. None of patients without cirrhosis died. Viral sequences showed the presence of hemagglutinin mutation D222G in two out of three fatal cases and S183P in seven out of eight infected patients. These mutants were not detected in the outpatients group. Even if A/H1N1/09 infection rate in hospitalized patients with and without cirrhosis was not significantly different, cirrhosis and D222G/S183P substitutions were significantly associated with severe disease and poor outcome, also suggesting fungal or bacterial superinfection and portal hypertension as risk factors for A/H1N1/09 disease severity in patients with cirrhosis. Vaccination, preventive and early treatment and a strict control of nosocomial spread should be activated carefully in patients with cirrhosis during epidemics influenza. J. Med. Virol. 85:1–7, 2012. © 2012 Wiley Periodicals, Inc.